Smart Specialization As A Tool For Development And Optimization Of Regional Development Policy Formation And Promotion Of Interregional Cooperation (Journal of Pharmaceutical Negative Results, 2023)
The aim of the article is to study the implementation of the concept of a smart specialization strategy (Strategy for Smart Specialization - S3) in the formation of regional development policy and promotion of interregional cooperation in the countries of the European Union (EU).The article claims that the main assumption of the concept of smart specialization is the allocation of unique strengths and opportunities specific to a particular territory. The choice of smart specialization is aimed at the optimal use of the region's resources through the best combination of the potential of science, education and economy. In addition, the implementation of smart specialization strategies in regions is not a single event, but a continuous management process. This approach emphasizes the importance of strategic interregional cooperation [21].In today's conditions, the implementation of cohesion policy in EU countries supports and encourages regions to improve the existing S3 and interregional cooperation.Research by a number of scientists in the field of the influence of smart specialization on economic changes in European regions has shown that this approach to management in an open economy is still not widespread. Scholars stress that the success of this approach depends on its ability to generate interregional cooperation and suggest sharing between regions common databases, industry/technology definitions, creating permanent forums for pooling and discussing common regional problems and challenges, and initiating a process exchange of information between regions on issues related to interregional cooperation. A deep review of S3 strategies is needed to improve them through joint policy development by different regions, taking into account their potential for cooperation [1].Despite the positive experience of implementing this effective instrument of regional development policy, there are ongoing debates, which are mainly focused on the problems of practical implementation of S3. In order to improve the capabilities of the concept of smart specialization, scientists propose the implementation of the construction of interregional S3, the improvement of management and financing mechanisms of interregional joint projects, the introduction of new provisions to support interregional cooperation [8].The article highlights how the approach of smart specialization was implemented in practice in some European regions [11], [12], [13], [14], [15]. The given examples show how interregional integration processes contribute to the successful implementation of the concept of smart specialization through involvement in interregional business networks and innovation systems. For this purpose, S3 entities use thematic partnerships in smart specialization.It is noted that success factors in fruitful interregional cooperation are a structure with strong leadership and management at the partnership level, as well as the presence of bodies - state bodies or cluster organizations - that manage the process and promote interregional cooperation. The study shows that well-structured governance is an important driving force for cross-regional initiatives where stakeholders develop a forward-looking vision that combines the strengths and potential of partners.